Between Understanding and Applying Knowledge: The role of Generative AI Among Young Professional Workers - Zamrudi, Zakky; Khuzaini, Khuzaini; Wicaksono, Teguh; Badjie, Gibriel (Universitas Tanjungpura, 2026)
The research aims to explore how the qualities of generative AI is integrated into daily professional practice to enhance the application of cognitive skills. The research involved 261 respondent of millennials and z generation employee. The instrument development in this research were drawn from cognitive knowledge domain and media richness theory compositing the AI media richness context. From the data analysis using PLS-SEM indicates that the over-relying on generative AI at certain level can dampen the cognitive knowledge mechanism which may also called as metacognitive laziness. This condition is need to be address to ensure employee cognitive ability to not only understand specific knowledge but also contextualize the knowledge to solve daily tasks as well as the strategic problem within the work environment.